Penggunaan Blogger sebagai media Promosi Digital untuk meningkatkan Branding UMKM Tahu Bakso Perintis - Zalfaa Salsabil Andiva; Zikriyya Turrabi’ah Hanif; Novadilastri Novadilastri; Sularno Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The Tofu Bakso Perintis MSME is proof that a simple business can grow significantly with the right strategy. In the digital era, promotions are no longer limited to direct sales, but can be expanded through effective blogger platforms to introduce products to a wider audience. By utilizing digital marketing, this MSME is able to build strong branding, create a positive image, and maintain consumer loyalty. Promotion through articles, social media, and creative content makes Tofu Bakso Perintis more widely known. In addition to offering a distinctive taste, this MSME also encourages local entrepreneurs to be unafraid of competition in the modern era. Combining product quality with a digital-based promotional strategy will help Tofu Bakso Perintis grow, not only in the local market but also with the opportunity to penetrate the national market.